3.4k views
2 votes
4 (2x-6)=10x-6. solve for x

User Alexeyss
by
6.1k points

1 Answer

5 votes

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

4*(2*x-6)-(10*x-6)=0


2x - 6 = 2 • (x - 3)

8 • (x - 3) - (10x - 6) = 0

-2x - 18 = -2 • (x + 9)

-2 • (x + 9) = 0

Solve : -2 = 0

This equation has no solution.
A a non-zero constant never equals zero.

Solving a Single Variable Equation :
Solve : x+9 = 0


Subtract 9 from both sides of the equation :
x = -9

User Shanil Arjuna
by
6.1k points